Astrakhan Yurt Tatars and the Peoples of Central Asia in the 16th – 18th Centuries - Ilya V. Toropitsyn (Журнал Фронтирных Исследований)
Astrakhan Yurt Tatars were in close contact with the peoples of Central Asia in the 16th – 18th centuries. Relations with the nearest geographical neighbors (Nogais, Kalmyks, Kazakhs) were influenced by the foreign policy situation, depending on which, periods of confrontation between the Astrakhan Tatars and nomadic peoples were replaced by peaceful coexistence. Astrakhan Tatars had more pragmatic relations with the inhabitants of the Central Asian khanates. Astrakhan Tatars maintained direct trade contacts with them, carrying out transactions both in Astrakhan and making caravan trips to Khiva and Bukhara. Due to the close interaction between them, trusty and family relations developed from time to time.